#TITLE_ALTERNATIVE# - Ariesta (NIM : 101 02 042), Mareiza
Abstract: Control chart is one of the primary techniques of statistical process control (SPC). This classical control charts are based on the assumption that the observations are normally distributed. In practice, normality often fails. Consequently, serious errors in estimating control limit often arise and the capability index will be far from their prescribed values, which finally make failure in process capability analysis. Improved data driven control chart, which choose between normal, parametric, and non parametric chart, have been proposed by Albers and Kallenberg in 2006 to solve this problem. The basic idea of this charts are correct the standard error from the classical control chart. In this thesis, will be applied this new method on the potency pertussis data of DTP vaccine PT. Biofarma where the data which meet the WHO specifications have lower capability index (capability index less than 1).